Categorization of differences of sex development among Egyptian children and the role of antimullerian hormone and inhibin B - Abdelghaffar, Shereen; AbdelMoneam, Engy Nasr; Hassanein, Samah A.; Radwan, Noha Abdelhalim; Mira, Marwa Farouk (Frontiers in Endocrinology, 2023)
Background: Differences of sex development (DSD) are congenital conditions linked to atypical development of chromosomal, gonadal, or anatomical sex. Objective: The aim of this study was to demonstrate our experiences at the Diabetes Endocrine and Metabolism Pediatric Unit (DEMPU), Faculty of Medicine, Cairo University in the field of DSD by focusing on the clinical presentation, laboratory profile, classification, and etiological diagnosis of these conditions. In addition, the present study intended to delineate the importance of serum anti-Müllerian hormone (AMH) and inhibin B in detecting the presence of functioning testicular tissue. Methods: This cohort study included 451 infants and children with various clinical presentations of DSD. The study performed a retrospective analysis on medical records of established DSD cases to evaluate the clinical importance of AMH and inhibin B. In addition, newly diagnosed patients were prospectively analyzed. Results: Three hundred thirty-six (74.5%) patients were 46,XY DSD, 98 (21.7%) were 46,XX DSD, 14 patients had other karyotypes and 3 had missing karyotypes. Among the 46XY DSD patients, the most common cause was partial androgen insensitivity deficiency. In contrast, congenital adrenal hyperplasia constituted the most common diagnosis in 46,XX DSD cases. The cut off value of serum AMH was 14.5 ng/ml with 100% sensitivity and 55.1% specificity. Conclusion: Partial androgen insensitivity was the most important cause of 46,XY DSD in Egyptian children, and congenital adrenal hyperplasia was the most common cause of 46,XX DSD. AMH was valuable in detecting functioning testicular tissue.